Kebijakan Jerman atas Pemberian Suaka Terhadap Pengungsi Asal Suriah Tahun 2015-2016 - Hendra Maujana Saragih; Rebekka Septiana Nababan (Himmah: Jurnal Kajian Islam Kontemporer, 2021)
The Refugees problem is no Longer a national problem but has become a global problem that must be resolved. Refugees are people who choose to leave their country of origin due to the safety of their own safety, conflicts that threaten their safety and their lives. The conflict in Syria has caused many Syrians to choose to flee to neighboring countries, including Europe. This study will analyze the politices implemented in dealing with refugees in 2015-2016 and is one of Germany’s responses to the refugees crisis that occurred in Europe. Germany’s policy has drawn criticsm from some Germans who are opposition parties and some European Union countries. Merkel, who is the German Chancellor who implemented the policy, did not mind the criticsm leveled at her policy. This study uses a qualitative this research using human security theory, refugee concept, national security theory, national interest theory.